Bankruptcy Institute (rehabilitation) of individuals — the final stage of creating an effective system of Bankruptcy (rehabilitation) in Kazakhstan - Seitimov , T.S. (BUKETOV BUSINESS REVIEW, 2019)
The article considers Institute of Rehabilitation and bankruptcy of individuals in Kazakhstan, its emergence as an economic phenomenon in the national economy of Kazakhstan, with the main goal to resolve the crisis of non-payments by individuals. Accelerated development of the market of credit services has meant that there are many economically active citizens now who do not calculate their financial capabilities, or simply not good enough understanding in the contractual loan structures implemented by commercial banks, in a situation inability to meet its financial obligations. Introduction of the institution of bankruptcy and rehabilitation of individuals expect many debtors: managers of large enterprises who apply themselves (usually in times of crisis), multi-million dollar loans, their colleagues — guarantors, individual entrepreneurs and ordinary citizens who could not pay their debts. Over the past years, the world community has been actively introducing the bankruptcy (rehabilitation) of individuals to solve a wide range of tasks, using mechanisms adapted to national priorities. Thus, the emergence of the institution of bankruptcy (rehabilitation) of individuals would be the final stage of establishing an effective bankruptcy system (rehabilitation) in Kazakhstan.